Comparative efficacy of flow diverter devices in the treatment of carotid sidewall intracranial aneurysms: a Retrospective, Multicenter Study - Dmytriw, Adam A.; Salim, Hamza; Musmar, Basel; Cancelliere, Nicole M.; Griessenauer, Christoph J.; Regenhardt, Robert W.; Jones, Jesse; Tutino, Vincent; Hasan, Zuha; Limbucci, Nicola; Lay, Sovann V.; Spears, Julian; et al. (Clinical neuroradiology, 2024)
Background The comparative efﬁcacy and safety of ﬁrst-generation ﬂow diverters (FDs), Pipeline Embolization Device (PED) (Medtronic, Irvine, California), Silk (Balt Extrusion, Montmorency, France), Flow Re-direction Endoluminal Device (FRED) (Microvention, Tustin, California), and Surpass Streamline (Stryker Neurovascular, Fremont, California), is not directly established and largely inferred. - Purpose This study aimed to compare the efﬁcacy of different FDs in treating sidewall ICA intracranial aneurysms. - Methods We conducted a retrospective review of prospectively maintained databases from eighteen academic institutions from 2009-2016, comprising 444 patients treated with one of four devices for sidewall ICA aneurysms. Data on demographics, aneurysm characteristics, treatment outcomes, and complications were analyzed. Angiographic and clinical outcomes were assessed using various imaging modalities and modiﬁed Rankin Scale (mRS). Propensity score weighting was employed to balance confounding variables. The data analysis used Kaplan-Meier curves, logistic regression, and Cox proportional-hazards regression. - Results While there were no signiﬁcant differences in retreatment rates, functional outcomes (mRS 0-1), and thromboembolic complications between the four devices, the probability of achieving adequate occlusion at the last follow-up was highest in Surpass device (HR: 4.59; CI: 2.75-7.66, p < 0.001), followed by FRED (HR: 2.23; CI: 1.44-3.46, p < 0.001), PED (HR: 1.72; CI: 1.10-2.70, p = 0.018), and Silk (HR: 1.0 ref. standard). The only hemorrhagic complications were with Surpass (1%). - Conclusion All the ﬁrst-generation devices achieved good clinical outcomes and retreatment rates in treating ICA sidewall aneurysms. Prospective studies are needed to explore the nuanced differences between these devices in the long term.
Gesehen am 14.04.2025